Partnership Morality as a Masterpiece of Business Performance - Ade, Sinar Hubtriyan; Wibowo, Bagus Yunianto; Kurniasih, Pritha (Ekonomi Syariah IAIN Kudus, 2024)
Partnership morality strengthened by spiritual capital is a variable built to mediate the effect of relational capital on business performance. The main purpose of this research is to analyze the essence and role, partially focusing on relational capital, spiritual capital, and partnership morality in business performance. In this study, the population was the owner of Batik SMEs in Pekalongan, Central Java, Indonesia, with as many as 247 Batik business units. The sampling method employs census sampling or turns the entire population into a research sample using a purposive sampling technique. The sample in this study was 101 owners of Batik SMEs in Pekalongan. Structural Equation Modeling (SEM) was used to analyze the data. The results of this study proved that partnership morality strengthened by spiritual capital variables can become a powerful mediation in the effect of relational capital on business performance. Partially, relational and spiritual capital has a significant positive effect on partnership morality. Meanwhile, spiritual and moral capital has a positive and significant impact on business performance, while spiritual capital does not affect business performance.